Giải pháp và định hướng phát triển dịch vụ thư viện số thông minh tại Thư viện Truyền cảm hứng Trường Đại học Tôn Đức Thắng - Nguyễn, Thị Thùy Dương (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
The purpose of this paper is to present the prerequisites and solutions to ensure the implementation of smart digital library services at Ton Duc Thang University INSPiRE Library in terms of building a smart management system, developing digital resources; investing and applying smart technologies; Servers and the internet; Create a team of professional librarians to meet the requirements of smart services. Moreover, this paper provides a general view of the 2022 - 2037.